Targeting Antibodies to Carbon Nanotube Field Effect Transistors by Pyrene Hydrazide Modification of Heavy Chain Carbohydrates - Steingrimur Stefansson; Hena H. Kwon; Saeyoung Nate Ahn (Journal of Nanotechnology)
Many carbon nanotube field-effect transistor (CNT-FET) studies have used immobilized antibodies as the ligand binding moiety. However, antibodies are not optimal for CNT-FET detection due to their large size and charge. Their size can prevent ligands from reaching within the Debye length of the CNTs and a layer of charged antibodies on the circuits can drown out any ligand signal. In an attempt to minimize the antibody footprint on CNT-FETs, we examined whether pyrene hydrazide modification of antibody carbohydrates could reduce the concentration required to functionalize CNT circuits. The carbohydrates are almost exclusively on the antibody Fc region and this site-specific modification could mediate uniform antibody orientation on the CNTs. We compared the hydrazide modification of anti-E. coli O157:H7 polyclonal antibodies to pyrenebutanoic acid succinimidyl ester-coated CNTs and carbodiimide-mediated antibody CNT attachment. Our results show that the pyrene hydrazide modification was superior to those methods with respect to bacteria detection and less than 1 nM labeled antibody was required to functionalize the circuits.